2021
DOI: 10.1021/acs.est.1c00804
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Oxide Nanomaterial, an Alternative for Commercial Copper Bactericides: Field-Scale Tomato Bacterial Spot Disease Management and Total and Bioavailable Metal Accumulation in Soil

Abstract: Copper (Cu) is the most extensively used bactericide worldwide in many agricultural production systems. However, intensive application of Cu bactericide have increased the selection pressure toward Cu-tolerant pathogens, including Xanthomonas perforans, the causal agent of tomato bacterial spot. However, alternatives for Cu bactericides are limited and have many drawbacks including plant damage and inconsistent effectiveness under field conditions. Also, potential ecological risk on nontarget organisms exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Field trials demonstrated that ZnO NPs reduced grapefruit canker incidence to a greater extent than did cuprous oxide and cuprous oxide/zinc oxide bactericides. Liao et al demonstrated in a field experiment that twice-weekly applications of 200 μg/mL nanoscale MgO significantly reduced disease severity of tomato bacterial spot caused by Xanthomonas perforans by 29–38% compared to the conventional Cu bactericide Kocide 3000 …”
Section: Resultsmentioning
confidence: 99%
“…Field trials demonstrated that ZnO NPs reduced grapefruit canker incidence to a greater extent than did cuprous oxide and cuprous oxide/zinc oxide bactericides. Liao et al demonstrated in a field experiment that twice-weekly applications of 200 μg/mL nanoscale MgO significantly reduced disease severity of tomato bacterial spot caused by Xanthomonas perforans by 29–38% compared to the conventional Cu bactericide Kocide 3000 …”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al 41 discovered that 5.0 mg L −1 Cu NPs decreased the metabolic activity and abundance of anammox bacteria. According to Liao et al , 42 MgO NPs are considered alternative materials for copper-based bactericides. Furthermore, the United States Food and Drug Administration (FDA) states that MgO NPs are a safe material, which indicates that the amount of used MgO NPs will greatly increase in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, the absence of streptomycin and copper-resistant strains in some countries in Africa provides a window for the careful deployment of antibiotics and copper-based formulations in bacterial spot disease management. Recent advances in small molecules and nano-formulations may provide additional opportunities for the management of bacterial spot disease in the future ( Liu et al, 2019 ; Liao et al, 2021 ; Qiao et al, 2021 ; Srivastava et al, 2021 ).…”
Section: Efforts To Manage Bacterial Spot Disease In Africamentioning
confidence: 99%